Full-Thickness Peroneus Longus Tendon Autograft Harvest - Carlos E. Franciozi MD, PhD; Enzo S. Mameri MD, MSc; Felipe C. Schumacher MD; Marcos V. Credidio MD; Marcelo S. Kubota MD; Marcus V. Luzo MD, PhD (SAGE Publishing, 2023)
Background: Despite extensive evidence of excellent biomechanical and clinical outcomes of ligament reconstructions with bone-patellar tendon-bone, hamstring tendon, and quadriceps tendon autografts, these are not without limitations, including knee-related donor site morbidity, decreased range of motion, and potential for anterior knee pain. Therefore, researchers have explored other options, including the peroneus longus (PL) autograft. Indication: Anterior cruciate ligament (ACL) reconstruction (both primary and revision), as well as multiligament reconstruction, particularly in areas where access to allografts is limited. Surgical Technique: A 3-cm longitudinal skin incision is placed 2 fingerbreadths (or 3 cm) proximal to the tip of the lateral malleolus, and 3 mm posterior to the fibula. The PL and peroneus brevis tendons are identified and isolated, followed by a tenodesis at the distal limit of the incision. The PL is whipstitched proximal to the tenodesis site, and then incised between the tenodesis and whipstitched portion. A closed tendon stripper is inserted and advanced proximally until the PL graft is released. Discussion/Conclusion: PL autograft harvest has been shown to generate thicker and longer grafts relative to the semitendinosus, with demonstrated efficacy in terms of both biomechanical and clinical outcomes. Current literature points largely to a good safety profile, although there is still conflicting evidence in terms of foot and ankle morbidity and no mid- to long-term follow-up data available. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form.